I am N : inspiring stories of Christian facing Islamic extremists - The Voice of the Martyrs (Colorado Springs, Colo : David C. Cook, 2016)
" 'I Am N' reminds us that we are each 'n,'-- the Arabic letter radical Muslims use to identify followers of Jesus of Nazarene. Wherever we live, we have camaraderie with those who are persecuted. So come meet their families. Read their stories. And deepen your faith in God who gives us the courage to shine in a dark and hurting world"--Page 4 of cover.
Contents: Introduction: The story behind the stories -- Part I: Sacrifice -- Part II: Courage -- Part III: Joy -- Part IV: Perseverance -- Part V: Forgiveness -- Part VI: Faithfulness.
Includes bibliographical references
Keywords: Christian martyrs -- Islamic countries -- Biography; Missions to Muslims; Christianity and other religions -- Islam; Islam -- Relations -- Christianity